2020
DOI: 10.1007/s13577-020-00341-x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-related hormones as potential markers of hypoxia/ischemia

Abstract: This study aimed to investigate the usefulness of the thyroid-related hormones as markers of acute systemic hypoxia/ischemia to identify deaths caused by asphyxiation due to neck compression in human autopsy cases. The following deaths from pathophysiological conditions were examined: mechanical asphyxia and acute/subacute blunt head injury; acute/subacute non-head blunt injury; sharp instrument injury as the hemorrhagic shock condition; drowning as alveolar injury; burn; and death due to cardiac dysfunction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Moreover, a few clinical studies, including randomized controlled trials [ 47 , 48 ], reported the therapeutic effects of the improvement of blood flow in the inner ear using betahistine in BPPV patients [ 49 ]. Several previous studies have suggested an association between abnormal levels of thyroid-related hormones and cardiovascular circulations [ 50 , 51 ]. Some prior studies have proposed increased thyroid-related hormones, including T3 and T4, in conditions of acute systemic ischemia [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a few clinical studies, including randomized controlled trials [ 47 , 48 ], reported the therapeutic effects of the improvement of blood flow in the inner ear using betahistine in BPPV patients [ 49 ]. Several previous studies have suggested an association between abnormal levels of thyroid-related hormones and cardiovascular circulations [ 50 , 51 ]. Some prior studies have proposed increased thyroid-related hormones, including T3 and T4, in conditions of acute systemic ischemia [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have suggested an association between abnormal levels of thyroid-related hormones and cardiovascular circulations [ 50 , 51 ]. Some prior studies have proposed increased thyroid-related hormones, including T3 and T4, in conditions of acute systemic ischemia [ 50 ]. On the other hand, reduced levels of thyroid-related hormones were also related to cardiovascular compromise [ 9 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A brief review of the recent literature revealed just a small number of articles addressing asphyxia through experimental protocols. Several approaches have been proposed 1 7 , mainly focused on the effects of asphyxial mechanisms, while little is known about the real-time biological modifications that occur during hypoxic-ischaemic insult. It was recently demonstrated 8 that only exceptionally long asphyxial periods can produce lungs histological modifications, whilst alterations can be observed at cellular and, especially, molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier report we found blood and cerebrospinal fluid (CSF) to have increased levels of triiodothyronine (T3) and thyroxine (T4). Thyroid gland secretions were high during acute hypoxic/ischemic conditions, regardless of any mechanical stimuli such as cervical compression [8]. We also found an increase in the pituitary gland blood-to-CSF transport of prolactin (PRL).…”
Section: Introductionmentioning
confidence: 72%
“…As a result, we have conducted several studies designed to investigate endocrine system abnormalities that occur due to systemic hypoxia [8][9][10]. In an earlier report we found blood and cerebrospinal fluid (CSF) to have increased levels of triiodothyronine (T3) and thyroxine (T4).…”
Section: Introductionmentioning
confidence: 99%